Challenges to implementing the food-based dietary guidelines in the South African primary school curriculum: a qualitative study exploring the perceptions of principals and curriculum advisors. Issue 1 (2nd January 2017) - Nguyen, Kim Anh; De Villiers, Anniza; Fourie, Jean Marie; Hendricks, Michael
Abstract : Objectives: The South African food-based dietary guidelines (FBDG) were developed and implemented to promote healthy lifestyles in the population along with preventing non-communicable diseases and other forms of diet-related illness. The FBDG were recommended for implementation within the national school curriculum. The objective of this study was to explore perceived challenges to successful implementation of these guidelines in the primary school curriculum. Design: This qualitative study gathered data via semi-structured individual interviews. Data were transcribed and analysed with ATLAS.ti software, using a thematic approach. Setting: Public primary schools located in three education districts in the Western Cape, South Africa. Subjects: Principals at twelve schools from communities with different socioeconomic statuses, and five curriculum advisors of relevant subjects from provincial and district levels. Outcomes measures: Perceived barriers to implementing FBDG in the primary school curriculum. Results: A lack of knowledge and/or expertise related to the FBDG by educators, time constraints within the teaching programme and lifestyle related factors of educators, parents and learners emerged as the three main challenge themes from the interviews. A lack of resources was identified as an additional theme. Conclusions: The principals and curriculum advisors anticipated many barriers to the success of implementing nutrition education using the FBDG in the primary school curriculum. Adequately addressing such barriers through improved awareness and knowledge of the FBDG by school staff could improve the potential of using the FBDG as a nutrition education tool in primary schools in South Africa.